Measuring the needs of dementia patients' caregivers: An assessment study from King Abdul-Aziz Medical City, Jeddah, Saudi Arabia [version 2; peer review: 2 approved, 1 approved with reservations] - Amal Al Suliman; Arwa Alotaibi; Waad Bin Afif; Ahmed Mkrshy; Ahoud Altamimi; Faris Baawad; Somaya Al Zhrani; Athbi Alenizi; Khlood Aldhamen; Rokaya Alghamdi; Abdulaziz Fadhel; Khalid Almalki; et al. (F1000Research)
Background Globally, dementia is estimated to become more prevalent as the population is aging. Patients with dementia are demanding on the long-term care from their caregivers. In order to maintain their well-being and minimize the impacts of long-term care, caregivers need comprehensive and supportive health services. This study aimed to improve and redesign the current healthcare service by assessing the needs of Saudi dementia patients’ caregivers using carers’ needs assessment for dementia (CNA-D). Methods Through a cross-sectional design and convenient sampling technique (non-probability Sampling), this study was carried out in two Saudi home care centers. The caregivers who fulfilled the inclusion criteria (n=276) were enrolled in the study and completed the interview questionnaire. Data collection lasted for two months (September and October 2022). A Chi-square test was performed to determine the statistical significance between participants’ responses and their demographic data. Results The majority of caregivers were females (76%). Their mean age was 38 years, ranging from 21 to 67 years. Two-thirds of caregivers spent more than one year on direct caregiving. About 60% of patients were male, and half were grandparents. Most caregivers (71%) did not live with their patients in the same household. Although caregivers rated all the addressed 13 needs in the present study as important, knowing more about the diseases was most important among caregivers of high education level. Further, long-term care gave caregivers more experience and reduced the need for practical support services. Conclusion The results show that the principal caregiver in Saudi families were females, and a large proportion of dementia patients were males. There were variations in rating the importance of the addressed needs, which were associated with caregivers’ demographic characteristics. The findings of this survey demonstrate the importance of assessing the needs of family caregivers when developing social and healthcare services.